2018
DOI: 10.1186/s12891-018-1998-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mesenchymal stem cells obtained by suspended culture of synovium from patients with rheumatoid arthritis and osteoarthritis

Abstract: BackgroundMobilization of mesenchymal stem cells (MSCs) from the synovium was revealed using a “suspended synovium culture model” of osteoarthritis (OA). The pathology of rheumatoid arthritis (RA) differs from that of OA. We investigated whether mobilization of MSCs from the synovium also occurred in RA, and we compared the properties of synovial MSCs collected from suspended synovium culture models of RA and OA.MethodsHuman synovium was harvested during total knee arthroplasty from the knee joints of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Most previous clinical studies of the synovial expression of VEGF and CD31 in RA had a cross-sectional designs [24,25], The results of the present study clearly showed that as disease progressed in OIA rabbits, the synovium developed more new blood vessels, and there was increased PDI grade, and increased disease score. These rabbits also had a positive correlation of MVD (CD31 positivity) with disease severity based on PDI grade.…”
Section: Ceus Imagingsupporting
confidence: 65%
“…Most previous clinical studies of the synovial expression of VEGF and CD31 in RA had a cross-sectional designs [24,25], The results of the present study clearly showed that as disease progressed in OIA rabbits, the synovium developed more new blood vessels, and there was increased PDI grade, and increased disease score. These rabbits also had a positive correlation of MVD (CD31 positivity) with disease severity based on PDI grade.…”
Section: Ceus Imagingsupporting
confidence: 65%
“…We con rmed that MSCs migrated along the gradient of FBS used as a positive control. This model had advantages of requiring only a small amount of medium and exhibiting a more uniform distribution of cells when compared to the suspended synovium culture model reported previously [10,11]. The synovial MSCs continued to migrate for the entire 48 h of the experiment, indicating that the chemoattractant gradient was maintained for that duration.…”
Section: Discussionmentioning
confidence: 80%
“…We previously developed a suspended synovium culture model for screening of drugs that could induce MSC mobilization from synovium [10,11]. The model consisted of one gram of human synovium suspended with a thread in a bottle containing 40 mL of culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there exist multiple studies presenting different phenotypes and topographies of MSCs in human synovium (Sivasubramaniyan et al, 2012;O'Brien et al, 2017;Mizuno et al, 2018;Affan et al, 2019) or rodent synovium (Roelofs et al, 2017); and their relationships with synovial fibroblasts (Croft et al, 2019), which may be pro-inflammatory, remain unclear. In the future, it would be interesting to establish which subset of synovial MSCs may be preferentially shed into the fluid, using recently developed in vitro methodologies (Kohno et al, 2018). Endogenous manipulations of the osteoarthritic synovium toward inflammation inhibition and increased MSC shedding into the fluid could be the next step toward KJD efficacy augmentation.…”
Section: Discussionmentioning
confidence: 99%